2020
DOI: 10.1177/2045894020922810
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis signal‐regulating kinase 1 inhibition in in vivo and in vitro models of pulmonary hypertension

Abstract: Pulmonary arterial hypertension, group 1 of the pulmonary hypertension disease family, involves pulmonary vascular remodelling, right ventricular dysfunction and cardiac failure. Oxidative stress, through activation of mitogen-activated protein kinases is implicated in these changes. Inhibition of apoptosis signal-regulating kinase 1, an apical mitogen-activated protein kinase, prevented pulmonary arterial hypertension developing in rodent models. Here, we investigate apoptosis signal-regulating kinase 1 in pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“… 37 In the current study, rPASMCs proliferated in response to 1% FBS to a similar degree under both normoxic and hypoxic conditions. While our finding that rPASMCs do not proliferate in response to hypoxia is in agreement with some previous studies, 17 , 38 others have shown hypoxic-induced proliferation of rPASMCs. You et al.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“… 37 In the current study, rPASMCs proliferated in response to 1% FBS to a similar degree under both normoxic and hypoxic conditions. While our finding that rPASMCs do not proliferate in response to hypoxia is in agreement with some previous studies, 17 , 38 others have shown hypoxic-induced proliferation of rPASMCs. You et al.…”
Section: Discussionsupporting
confidence: 94%
“…17 In vitro rPAFs derived from sugen5416/ hypoxic rats displayed increased proliferation, migration and p38 MAPK expression; these effects were not present in rPAFs derived from sugen5416/hypoxic rats dosed with the ASK1 inhibitor, GS-444217. 17 Using lung tissue from these sugen5416/hypoxic rats, we investigated if the changes seen in vivo and in vitro also coincided with an altered connexin expression. We observed no changes in GJA1 (Cx43) gene expression in lung tissue from sugen5416/hypoxic rats.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Reactive oxygen species are also involved in regulation of cell signaling through the mitogen-activated protein kinase (MAPK) pathway, which is associated with a variety of cellular effects, including proliferation, survival, death, and transformation ( Son et al, 2013 ). One study on rats exposed to hypobaric hypoxia showed that the constitutive MAPK termed apoptosis signal-regulating kinase 1 (ASK1), which is known to be critical in the remodeling processes of pulmonary artery hypertension, participates in PASMC proliferation through activation of p38 MAPK and endothelin-1 (ET-1) in response to oxidative stress ( Wilson et al, 2020 ).…”
Section: Oxidative Stressmentioning
confidence: 99%